KEBEBASAN EMOSI ANAK DALAM BERMAIN DITINJAU DARI TEMPAT BERMAIN DAN JENIS KELAMIN - Dhaniswara Widyaningsih, Bernadeta (Widya Warta, 2011)
This study was designed to see how emotional freedoms of the third up to ninth year students were different one another, viewed from play area and sex. Social changes led to condition, where there was no difference of children's emotional freedoms in play seen from sex. The respondents of this research were 49 girls and 59 boys (who lived in the rural area of Madiun Regency) categorized according to their play area and sex. Emotional freedom in play was measured by the use of a scale of emotional freedom. The data analysis made use of ancova by SPSS 14.0. The result showed that there was a very significant difference of freedoms of children's emotions in play in terms of play area (F = 34.151; p <0.01) and there was no difference of their emotional freedoms in terms of sex (F = .704; p> 0.05).